2009
DOI: 10.1302/0301-620x.91b12.22139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological follow-up of the Aequalis third-generation cemented total shoulder replacement

Abstract: There are no long-term published results on the survival of a third-generation cemented total shoulder replacement. We describe a clinical and radiological study of the Aequalis total shoulder replacement for a minimum of ten years. Between September 1996 and May 1998, 39 consecutive patients underwent a primary cemented total shoulder replacement using this prosthesis. Data were collected prospectively on all patients each year, for a minimum of ten years, or until death or failure of the prosthesis. At a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 36 publications
2
77
1
3
Order By: Relevance
“…This is consistent with the literature, in which the most common reasons for failure of hemiarthroplasties or total shoulder arthroplasties include superior migration or subluxation of the humeral head secondary to rotator cuff dysfunction occurring in 17% to 54% of patients [2,7,13,17,19,30,34] with the likelihood of a higher incidence with longer followup [5,34]. Our study showed that a modular stem designed for exchange has distinct advantages in the case of revision and that the quality of implantation (prosthetic height and torsion) at the index operation is important, because improper positioning can mandate stem exchange even in a system designed to allow stem preservation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the literature, in which the most common reasons for failure of hemiarthroplasties or total shoulder arthroplasties include superior migration or subluxation of the humeral head secondary to rotator cuff dysfunction occurring in 17% to 54% of patients [2,7,13,17,19,30,34] with the likelihood of a higher incidence with longer followup [5,34]. Our study showed that a modular stem designed for exchange has distinct advantages in the case of revision and that the quality of implantation (prosthetic height and torsion) at the index operation is important, because improper positioning can mandate stem exchange even in a system designed to allow stem preservation.…”
Section: Discussionsupporting
confidence: 92%
“…In the majority of patients, revision is performed to treat cuff failure with associated instability [2,19,30,34] or glenoid erosion [3]. With instability, secondary cuff failures, or glenoid erosion, the humeral component often is well fixed in the humeral shaft.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients maintain their improvements over the long term; however, complications and failures do occur, and these have been associated with component malposition, glenoid failure, and glenohumeral malalignment [4]. Additionally, complications such as prosthetic loosening, periprosthetic fractures, rotator cuff tears, and instability have an adverse effect on pain and function [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…McCoy et al found good pain relief in up to 93% after surgery [4]. However, despite high patient satisfaction and good pain relief, function is unpredictable and often poor, with patients in some series averaging elevation below the horizontal [5][6][7]. Barrett et al reported active forward flexion averaged 34 degrees in 140 anatomical shoulder replacements where 50% of patients had significant cuff pathology [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cuff tears in rheumatoid patients are extremely common (20%-100%) [6,9,10] and when present, lead to inferior results of joint replacement due to poor pain relief, superior humeral migration, increased shear forces, eccentric wear, instability, early failure and glenoid loosening rates as high as 50% [6,7,[11][12][13][14]. It is therefore clear that the rotator cuff is an important prognosticator of outcome.…”
Section: Introductionmentioning
confidence: 99%